PENYULUHAN PENGELOLAAN SAMPAH GUNA MENCIPTAKAN LINGKUNGAN BERSIH DAN NYAMAN DI KECAMATAN BAYONGBONG - Purnamasari, Ismi; Mubarok, Gian Ikhsanul; Sari, Wanda; Praharja, Yoga; Febriansyah, Arif Sani; Nasihin, Muhammad; Yusup, Cahya Purnama; Akmal, M.; Permana, Dimas Satia; Kirani, Garnis; Dewi, Erika Puspa; Yasin, Yasin; Kustiana, Ruli M; Sidqi, Muhammad Affan Al; Humaira, Asma Rani Rosalba; Ajis, Alus; Maulana, Haris; Nafisa, Delia Yulianti; Fadhilah, Muhamad Yassin Al; Supriadi, Ari (Institut Teknologi Garut, 2023)
An environment that is clean from rubbish is an environment that everyone hopes for. The amount of waste produced by humans will increase in proportion to the increase in population, type of activity and level of population consumption of goods. Mekarjaya Village is a village in Bayongbong sub-district, Garut Regency which has a population of 1187 people. With this population, it is very likely that waste will accumulate if it is not managed properly. At the Garut Institute of Technology's Thematic KKN activities in 2023, it was identified that there was a buildup of rubbish in a location that had not been organized. Therefore, one of the community service activities will be activities that focus on environmental cleanliness. This is done with the aim of creating a more organized environment and a cleaner and healthier environment. To achieve this goal, joint environmental cleaning activities were carried out, providing rubbish bins and waste sorting education to educate residents about the importance of waste management to achieve environmental cleanliness.